Analyses of FLG mutation frequency and filaggrin expression in isolated ichthyosis vulgaris (IV) and atopic dermatitis‐associated IV. (1st April 2013) - Li, M.; Cheng, R.; Shi, M.; Liu, J.; Zhang, G.; Liu, Q.; Yu, H.; Yao, Z.
Summary: Background  Ichthyosis vulgaris (IV; OMIM 146700) is a very common inherited skin disorder. Loss‐of‐function mutations in the filaggrin gene ( FLG ) have been identified as the cause of IV. In a previous study, we found that the percentage of FLG null mutations was lower in IV associated with atopic dermatitis (AD) than in IV not associated with AD (isolated IV). We speculated that some clinical manifestations of IV in patients with AD are not induced by FLG mutations. Objectives  In order to clarify this issue, we collected 21 IV pedigrees, 33 patients with sporadic isolated IV and 116 patients with AD‐associated IV to analyse FLG mutation frequency and filaggrin expression in isolated IV and AD‐associated IV. Methods  A comprehensive sequencing of the FLG gene in all patients was performed using an overlapping polymerase chain reaction (PCR) strategy. We also studied the immunohistochemistry of profilaggrin/filaggrin protein expression in the skin and measured the mRNA expression using real‐time PCR in seven patients, including one patient with IV harbouring the mutation c.3321delA, two patients with AD‐associated IV harbouring c.3321delA and c.6834del5, and four patients with AD‐associated IV without FLG mutations. Results  The percentage of mutations in the FLG gene was 74% and 43% in patients with isolated IV and patients with AD‐associated IV, respectively. Immunohistochemical staining revealed that profilaggrin/filaggrin peptides were remarkably reduced in the epidermis of all the patients. All the patients with either AD or IV showed lower FLG mRNA expression compared with the normal control. Conclusions  These results indicate that factors other than FLG gene mutations can downregulate profilaggrin/filaggrin expression, leading to the ichthyosiform phenotype in the context of AD. Abstract : What's already known about this topic? FLG mutations are the cause of ichthyosis vulgaris (IV) and the strongest genetic risk for atopic dermatitis (AD). T helper 2 cytokines and tumour necrosis factor‐α may reduce filaggrin expression. What does this study add? The frequency of FLG mutations in isolated IV is much higher than in AD‐associated IV.  Factors other than FLG gene mutations can downregulate profilaggrin/filaggrin expression, leading to the ichthyosiform phenotype in the context of AD.